A comprehensive review of obstacles and drivers to building energy-saving technologies and their association with research themes, types of buildings, and geographic regions - Cristino, T. M. [UNESP]; Lotufo, F. A. [UNESP]; Delinchant, B.; Wurtz, F.; Faria Neto, A. [UNESP] (Elsevier, 2021)
The building sector has played an important role in energy consumption over the last few decades, demanding actions to decrease it. A way to reach this goal, without affecting the occupants’ welfare, is the adoption of building energy-efficient (BEE) technologies. There are several of these technologies available, bringing lots of benefits. However, there are barriers that hinder their adoption. Before overcoming such barriers, it is necessary to know them. Thus, after examining 450 publications, from 2000 to 2018, only eight presented some kind of taxonomy to the barriers, ranging from three to five categories, showing that some barriers were perhaps not considered. The dependence relationship of the barriers and the types of buildings and geographical regions as well as their evolution has not yet been evaluated. The recommendations to overcome such barriers are spread throughout the literature and have not yet been compiled. This review gathered 105 barriers that were grouped into six categories (Financial, Market, Technological, Professional, Political and Behavioural), followed by their respective timelines, as well as the dependence relationship of them and the types of buildings and geographical regions. A compilation of the strategies to overcome such barriers is also presented. These results, besides supporting the formulation of policies for the adoption of BEE technologies, clarify the structure of each group of barriers and allow researchers to identify the most relevant ones for their scenario followed by the starting point to overcome them, focusing their attention on neuralgic points.
Keywords: Barriers; Building energy efficiency; Buildings; Energy efficiency; Energy saving; Energy-efficient technologies